Boxing trauma prevention = (NpROF)QÆLAKTIKA TRAWMATIZMU W BOKSÆ (B/s)E - Bondarenko, Maxim (2018)
The article shows the importance of custom made mouth guards in boxing. It has been shown that such guards have the potential to lower neurologic damage by slowing down and softening the impact to the jaw and to the base of the skull thus reducing the energy delivered to target
(Nu STATT)QÆ WISWÆTLENO WAVLIWÆSTX ZASTOSUWANNQ ÆNDIWÆDUALXNIH ZAHISNIH KAP U BOKSÆ(B. (NdOWEDENO(B, (N]O ÇH WIKORISTANNQ ZNIVUÃ RIZIK NEWROLOGÆ^NIH PORU[ENX(B, (NSPOWÆLXN@Ã TA POM(B'(NQK[UÃ ENERGÆ@ UDARU(B, (NQKA NEGATIWNO WPLIWAÃ NA ]ELEPU TA OSNOWU ^EREPAs)E
(Nb)QÆBLÆOGR(B. (NW KÆNCÆ ST(B.s)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NBOKSs; (NTRAWMAs; (NZAHISTs; boxing; guards; trauma